Pendampingan Sertifikasi Halal Pada UMKM Makanan Ringan Di Desa Bansari Kecamatan Bansari Kabupaten Temanggung - Gunarti Ika Pradewi; Muchammad Iqbal Chailani; Siti Arifah (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2023)
Nowadays, halal products have become a lifestyle as well as a necessity for people in Indonesia. The government has tried to fulfil these needs by providing halal certification. This effort certainly requires the participation of various parties including academics. To support these efforts, the author conducted community service in Bansari village related to obtaining halal certification for existing MSMEs. Assistance is carried out using the PAR (Participatory Action Research) method which starts from the stages of (1) Community Research Social Problem Diagnostic, (2) Community Strategic Planning, (3) Community Resource Mobilisation, and (4) Reflection.  The results of the assistance carried out are first, the Bansari Village community has insight into the processing and presentation of halal products that have been determined by the government; second, the community has an NIB; third, the Bansari village community becomes skilled in processing and marketing their processed products so that they can be accepted by the market both offline and online markets.Keywords: Halal certification, Halal products, UMKMAbstrakSaat ini produk halal menjadi gaya hidup sekaligus kebutuhan bagi masyarakat di Indonesia. Pemerintah telah berupaya memenuhi kebutuhan tersebut dengan menyediakan sertifikasi halal. Upaya tersebut tentu membutuhkan partisipasi berbagai pihak termasuk akademisi. Untuk mendukung upaya tersebut penulis melakukan pengabdian kepada masyarakat di desa Bansari terkait dengan perolehan sertifikasi halal bagi UMKM yang ada. Pendampingan dilakukan dengan menggunakan metode PAR (Participatory Action Research) yang dimulai dari tahap (1) Community Research Social Problem Diagnostic, (2) Community Strategic Planning , (3) Community Resource Mobilication, dan (4) Reflection.  Hasil dari pendampingan yang dilakukan adalah pertama, masyarakat Desa Bansari memiliki bekal wawasan dalam pengolahan dan penyajian produk halal yang telah ditetapkan oleh pemerintah; kedua, masyarakat memiliki NIB; ketiga, masyarakat desa Bansari menjadi terampil dalam mengolah dan memasarkan produk olahan mereka agar bisa diterima oleh pasar baik pasar offline maupun online.Kata Kunci: Sertifikasi halal, Produk halal, UMKM